AB0505 Case report of allogeneic unrelated-donor mesenchymal stem cells (msc) infusion in systemic sclerosis (ssc). (23rd January 2014) - Chakr, R.; Pavan, T.; Siqueira, I.; Zanchet, D.; Calegaro, N.; Andrade, N.; Neto, G.; Neves, M.; Bredemeier, M.; Palominos, P.; Kohem, C.; Amorin, B.; et al.
Abstract : Background: Intravenous MSC infusion has been reported occasionally in SSc treatment. To our knowledge this is the first case report of allogeneic unrelated-donor intravenous MSC infusion in SSc without immunosuppresive induction of MSC transplantation. Objectives: To report the case of a cutaneous diffuse SSc patient with severe lung and skin manifestations treated with MSC infusion. To review the current literature on intravenous MSC infusion for SSc. Methods: Literature review and multidisciplinary discussion were thoroughly performed before treatment protocol was approved by institutional ethics committee and patient and family signed informed consent form. Results: A 36 year-old white female with a 10-year history of diffuse SSc manifested by severe scleroderma (Rodnan score 47/51), skin ulcers and extensive lung fibrosis refractory to methotrexate, azathioprine and cyclophosphamide received two infusions of allogeneic unrelated-donor 2x10 6 /Kg MSC. No immediate reactions occurred. Despite treatment, patient died of refractory shock and respiratory failure. No infections or tomographic changes had been detected. In other reports, fatality was not attributed to MSC infusion (Table ). Conclusions: Intravenous MSC infusion has been reported in few cases of SSc. In previous allogeneic related-donor or autologous MSC infusions and in the present allogeneic unrelated-donor MSC infusion reports, patients were heterogeneous and treatment protocols differed significantly. Larger studies are needed to validate clinical efficacy and safety and to standardize treatment protocol of MSC infusion in SSc. References: Christopeit M, Schendel M, Foll J, et al . Marked improvement of severe progressive systemic sclerosis after transplantation of mesenchymal stem cells from an allogeneic haploidentical-related donor mediated by ligation of CD137L. Leukemia. 2008 May;22(5):1062-4. Guiducci S, Porta F, Saccardi R, et al . Autologous mesenchymal stem cells foster revascularization of ischemic limbs in systemic sclerosis: a case report. Ann Intern Med. 2010 Nov 16;153(10):650-4. Keyszer G, Christopeit M, Fick S, et al . Treatment of severe progressive systemic sclerosis with transplantation of mesenchymal stromal cells from allogeneic related donors: report of five cases. Arthritis Rheum. 2011 Aug;63(8):2540-2. Disclosure of Interest: None Declared